ANALYSIS OF POLYCYCLIC AROMATIC HYDROCARBON IN SOME MEAT PRODUCTS - Lukitaningsih, Endang; Sudarmanto, Bambang Sulistyo Ari; Noegrohati, Sri (Indonesian Journal of Pharmacy, 2001)
The polycyclic aromatic hydrocarbons (PAHs) are a class of organic compounds, composed two or more fused aromatic (benzene) rings, occurred in the environment due to incomplete combustion of organic matters such as forest fires, volcanic eruption, burning of fossil fuels and incorrect process of meat cooking (grilling, smoking, roasting). Healt concerns are focussed on the metabolite transformation of PAHs, which may have mutagenic, carcinogenic and terratogenic activity. Due to their hydophobicity, it is probable the compounds enter human food chain and accumulated in human lipid tissues. Therefore, environment pollution by PAHs must be considered. PAHs gain entry to human body through several routes including respiration, absorpsion through skin surface ang through food consumption that have been polluted with PAHs. In this study concentrations of PAHs (pyrene, perilene, benzo(a)anthracene, benzo(k)fluorantrene and benzo(a)pyrene) in traditional smoked meat, liquid smoked meat and roasted meat are determined. Determination of PAHs used gas chromatograph with OV 17 2% as a stationary phase, nitrogen as carrier gas and flame ionization detector. The results showed that PAHs concentrations in traditional smoked meat were higher than liquid smoked meat (41.19 ppb and 1.03 – 9.26 ppb). In the roasted meat, lipid concentration and roasting time influence PAHs concentration level.Keywords : polycyclic aromatic hydrocarbon, smoked meat, liquid smoke